Chronic Teacher Turnover in Urban Elementary Schools - Guin, Kacey (Education Policy Analysis Archives, 2004)
This study examines the characteristics of elementary schools that experience chronic teacher turnover and the impacts of turnover on a school’s working climate and ability to effectively function. Based on evidence from staff climate surveys and case studies, it is clear that high turnover schools face significant organizational challenges. Schools with high teacher turnover rates have difficulty planning and implementing a coherent curriculum and sustaining positive working relationships among teachers. The reality of these organizational challenges is particularly alarming, given that high turnover schools are more likely to serve low-income and minority students. The negative relationship between teacher turnover and school functioning, and the fact that turbulent schools are disproportionately likely to serve lowincome and minority students have important implications for both district and school-level policies. Specifically:Teacher turnover rates are one indicator of school health, which school districts should consider when focusing on school improvements. Districts need to begin by developing the means to identify individual schools that experience high levels of teacher turnover. Current district policies in implementing professional development for teachers in low-performing schools are inefficient when teachers do not remain in the schools in which they are trained. In order for low-performing schools to improve, districts need to consider providing incentive programs so that high quality teachers apply for, and remain in, these schools. Future research is needed to address the causal link between turnover, organizational functioning and student outcomes. Additionally, there is a need for research examining district policies that may facilitate teacher turnover within a district, including how districts place and transfer teachers, as well as how teachers’ salaries are budgeted.